2011
DOI: 10.1080/14786410903293191
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and chemical composition ofSideritis libanoticaLabill. ssp.linearis(Bentham) Borm. (Lamiaceae)

Abstract: Sideritis libanotica ssp. linearis was screened for the isolation of new natural antioxidant compounds. The antioxidant activity of flavones obtained from the methanol extract of the plant was evaluated in vitro using total antioxidant, reduction power and free radical scavenging activity. Results were compared with the positive controls of antioxidant standards (α-tocopherol and butylated hydroxytoluene). The results indicate that the flavones possess a higher antioxidant activity when compared to the other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Palmitic acid (14.34%) and oleic acid (13.14%) in S. libanotica ssp. linearis ; capric acid (42.72%) and steric acid (30.64%) in S. taurica ; linolenic acid (77.04 ± 2.07%) and oleic acid (18.83 ± 0.10%) in S. montana were determined as major fatty acids (Aboutabl et al, ; Demirtas et al, ; Emre, Kurşat, & Yılmaz, ).…”
Section: Resultsmentioning
confidence: 99%
“…Palmitic acid (14.34%) and oleic acid (13.14%) in S. libanotica ssp. linearis ; capric acid (42.72%) and steric acid (30.64%) in S. taurica ; linolenic acid (77.04 ± 2.07%) and oleic acid (18.83 ± 0.10%) in S. montana were determined as major fatty acids (Aboutabl et al, ; Demirtas et al, ; Emre, Kurşat, & Yılmaz, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that methanol extracts of Sideritis libanotica ssp. linearis , containing flavonoids, showed significant anticancer activity against three cell lines, namely Vero cells (African green monkey kidney), C6 cells (rat brain tumor) and HeLa cells (human uterus carcinoma) . It was observed that methanol extracts inhibited the proliferation of these cell lines in a dose‐dependent manner (from 25 to 250 µg mL −1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Sideritis species include flavonoids, terpenes, iridoids, coumarins, lignanes and sterols that are responsible constituents for their pharmacological properties (Gonzá lez-Burgos et al, 2011). Sideritis species have been reported to exhibit considerable biological activities such as antioxidant (Demirtas et al, 2011), antiproliferative (Demirtas et al, 2009), and antimicrobial (Yig it Hanog lu et al, 2017) effects. The crystal structure of 2--hydroxymanoyl oxide isolated from Sideritis perfoliata has been reported on by our group (Ç elik et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%